Do All Pediatric Femoral Shaft Fractures Need a Computed Tomography Scan of the Ipsilateral Femoral Neck? Calculating the Incidence of Concomitant Femoral Neck and Shaft Fractures. Issue 3 (26th March 2023) - Pradhan, Pratik; Townsend, Tracy K.; Cook, Danielle; Feldman, Lanna; Canizares, Maria Fernanda; Watkins, Colyn; Shore, Benjamin J.
Abstract : Background: In adults, the incidence of ipsilateral femoral neck fractures in the setting of femoral shaft fractures is reported to be as high as 9%; however, scant literature exists on the same clinical scenario in pediatric/adolescent populations. Therefore, the purpose of this study was to investigate the incidence of ipsilateral femoral neck fracture in the setting of femoral shaft fractures in children and adolescents treated in pediatric hospitals across the United States. Methods: The Pediatric Health Information System database was queried for patients aged 18 years or younger who were treated for a femoral neck, femoral shaft, and pertrochanteric femur fractures through an emergency department, inpatient, ambulatory surgery, or observation visit. Patients were identified using ICD-9 and ICD-10 diagnosis codes. Data from 49 pediatric hospitals between the years 2002 and 2020 were included. Incidence was calculated as the number of cases including the event divided by the total number of cases. Results: A total of 90, 146 records were identified from a cohort of 55, 733, 855 (0.16%). Distal femur fractures, pathologic fractures, and periprosthetic fractures were excluded, resulting in 65, 651 unique cases. Of the 65, 651 cases, 7104 (11%) were identified as isolated neck fractures. The combined incidence of femoral neck or pertrochanteric femur fractures in the setting of a femoral shaft fracture was 82.3 per 10, 000 cases (0.82%). Only 283 cases of concomitant femoral neck and shaft fractures were found among 55, 169 femoral shaft fractures (0.5%). Conclusions: The incidence of ipsilateral femoral neck or pertrochanteric femur fractures in the setting of a femoral shaft fracture is 82.3 per 10, 000 patients (0.82%) based on data from Pediatric Health Information System-participating institutions. The incidence of femoral neck/pertrochanteric femur fractures and femoral shaft fractures in children and adolescents is more than 10 times lower than reported for adults; therefore, the routine use of advanced diagnostic imaging in pediatric patients with femoral shaft fractures should be considered cautiously. Level of Evidence: Level IV; cross-sectional analysis.